Idea Fare - Larry A. Quinn; Harry A. Carey Jr.; John Philpot; Garth Ketemer; Ruth Thompson; Bill Fowell; Henry W. Corrow Jr. (Journal of Applied Communications, 1978)
Multiple articles that include descriptions of evaluations and test of information methods conducted by ACE members. Includes: On Dead Trees & Smudgy Ink, Keeping Pace with Exhibits, National ACE Media Sessions on Radio and Television, Publications, Graphics Design, Visual Aids Committee